1990
DOI: 10.1128/jcm.28.5.841-842.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the CMV-CUBE assay for detection of cytomegalovirus serologic status in marrow transplant patients and marrow donors

Abstract: We evaluated a new membrane dot immunobinding assay (CMV-CUBE; Difco Laboratories) for the detection of cytomegalovirus (CMV) antibody in marrow transplant patients and donors. The CMV-CUBE assay was compared with a commercially available enzyme immunoassay (EIA; CMV STAT) and a latex agglutination (LA; CMVScan) test. Serum samples were collected from 311 transplant patients and donors prior to transplantation. A total of 164 serum specimens were positive for CMV antibody by one or more of the three assays, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Detection of seroconversion is uncommon in the absence of a specific follow-up. Many data indicate that IgM also appears during nonprimary infection (8). Furthermore, a well-standardized commercial kit for detecting a particular antibody profile is not available (14).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of seroconversion is uncommon in the absence of a specific follow-up. Many data indicate that IgM also appears during nonprimary infection (8). Furthermore, a well-standardized commercial kit for detecting a particular antibody profile is not available (14).…”
Section: Discussionmentioning
confidence: 99%
“…The latex agglutination test, which is used in most laboratories, is a simple and rapid method for the determination of CMV immune status (2,8). However, there is some doubt as to whether all seronegative donors have never really had previous CMV infection, and the subsequent possibility of the presence of latent virus (7,16).…”
mentioning
confidence: 99%
“…As has been shown in several other studies [6,9,11,20], it is important to use a dependable serological assay for screening blood and organ donors to achieve a reduction of transmitted HCMV infection and HCMV disease in seronegative recipients at risk of primary infection. However, there is some debate about seronegative donors being free from previous HCMV infection and the possibility of presence of latent virus [10,28,29]. Using the DBH technique we found that in 9 out of the 45 (20%) patients HCMV genome could be detected.…”
Section: Discussionmentioning
confidence: 86%
“…After primary infection the virus persists in the host as a chronic or latent infection, which can periodically reactivate to an active infection. HCMV is known to be transmitted through blood transfusions [1,24] and transplanted organs [10,33] which can result in a severe HCMV disease, especially in immunosuppressed and seronegative patients [3,22]. Several studies indicate that in HCMV seropositive healthy individuals latent infection can be demonstrated by the presence of HCMV antigens.…”
mentioning
confidence: 99%